Acinetobacter baumannii Resistance: A Real Challenge for Clinicians - Rosalino Vázquez-López; Sandra Georgina Solano-Gálvez; Juan José Juárez Vignon-Whaley; Jorge Andrés Abello Vaamonde; Luis Andrés Padró Alonzo; Andrés Rivera Reséndiz; Mauricio Muleiro Álvarez; Eunice Nabil Vega López; Giorgio Franyuti-Kelly; Diego Abelardo Álvarez-Hernández; Valentina Moncaleano Guzmán; Jorge Ernesto Juárez Bañuelos; et al. (MDPI AG, 2020)
Acinetobacter baumannii (named in honor of the American bacteriologists Paul and Linda Baumann) is a Gram-negative, multidrug-resistant (MDR) pathogen that causes nosocomial infections, especially in intensive care units (ICUs) and immunocompromised patients with central venous catheters. A. baumannii has developed a broad spectrum of antimicrobial resistance, associated with a higher mortality rate among infected patients compared with other non-baumannii species. In terms of clinical impact, resistant strains are associated with increases in both in-hospital length of stay and mortality. A. baumannii can cause a variety of infections; most involve the respiratory tract, especially ventilator-associated pneumonia, but bacteremia and skin wound infections have also been reported, the latter of which has been prominently observed in the context of war-related trauma. Cases of meningitis associated with A. baumannii have been documented. The most common risk factor for the acquisition of MDR A baumannii is previous antibiotic use, following by mechanical ventilation, length of ICU/hospital stay, severity of illness, and use of medical devices. Current efforts focus on addressing all the antimicrobial resistance mechanisms described in A. baumannii, with the objective of identifying the most promising therapeutic scheme. Bacteriophage- and artilysin-based therapeutic approaches have been described as effective, but further research into their clinical use is required